Wavelength switching components for future photonic networks. - White, I.
This article provides a review of integrated laser and semiconductor optical amplifier components that have been configured to provide a variety of all-optical functions such as wavelength conversion, routing, signal regeneration, and add-drop multiplexing. The components have been devised so that they can be reliably and simply used within a multiwavelength network. The article introduces the components by outlining the current leading techniques for wavelength conversion using SOAs, namely by way of cross-gain modulation, cross-phase modulation, and four-wave mixing. The integrated SOA distributed feedback laser is then shown to provide excellent regeneration properties, not only overcoming fiber dispersion limitations but also polarization mode dispersion. Finally, the devices are shown to make possible a regenerative wavelength switching node where routing is achieved using a tunable laser to provide regenerative wavelength conversion followed by an arrayed waveguide router. This switch shows promise for use in future photonic packet switching architectures
Keywords: Add-drop multiplexing; All-optical functions; Arrayed waveguide router; Cross-gain modulation; Cross-phase modulation; Fiber dispersion; Four-wave mixing; Integrated SOA distributed feedback laser; Integrated laser components; Multiwavelength network; Photonic networks; Photonic packet switching architectures; Polarization mode dispersion; Regenerative wavelength conversion; Regenerative wavelength switching node; Semiconductor optical amplifier; Signal regeneration; Tunable laser; Wavelength conversion; Wavelength routing; Wavelength switching components